ROLE OF DISLOCATION METAMORPHISM IN ENDOGENIC ORE-FORMING PROCESSES WITHIN THE BELOZERSKA GREENSTONE STRUCTURE - Ruzina, M.; Tereshkova, O.; Bilan, N.; Zhiltsova, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The purpose of the paper is to define the genesis of epigenetic ore formations within the Belozerska greenstone structure (BGS). Methodology included determination of composition, structure, and relationship of geological and ore formations, and the study of composition of the formations of hydrothermal metasomatites. Analyzed type of mineralization has been revealed in different stratigraphic complexes throughout the entire territory of BGS, but most intensively it has been represented in footwall rocks of the South-Belozersk deposit. Anomalous zones have plate-shaped and block form, occur in multiple layers and parallel groups (bundles) with heavy pitch to the east and close to concordant bedding. Results. The complex mineralization of precious metals (PM) related to the hydrothermal metasomatic formations (listvenite-beresite, greisen and carbon formations) was identified within the Mykhailivka suite of Belozerska series. The material composition of the precious metal mineralization is characterized by two features – the predominant localization in the metasomatic listvenite-beresite formation and complex multi-stage nature of spatial combining four mineral assemblages of different age. The absence of not only genetic, but also hydrothermal paragenetic relation with magmatism is characteristic for the conditions of the hydrothermal mineralization in BGS. Dislocation metamorphism had the dominating role in the structure formation and developed after the regional metamorphism and irrespectively of it. Regional and local faults are ore-controlling structures, namely, they control both the position of BGS at the intersection of four deep fault systems and subordinate fault, fold and boudinage structures. Spatial combination of mineralization processes that are different in the type and age is associated with multiple manifestations of tectonic activity and the structural position of thick metabasite Konkska series under the substantially terrigenous Belozersk series. These fluid-explosive units identified within the Pereverzevska suite of Belozersk series are analogous to diamond prospecting visherite of the Urals and diamondiferous phyllite in Brazil in their morphological features, mineral composition and structure. Novelty. Factual background of the manifestations of dislocation metamorphism in deep faults within the study structure is set and proved its ore-forming role in the formation of complex epigenetic ore formations. Practical importance. Study results provide for the discovery of unconventional deposits of PM in black-shale strata and diamond prospecting formations of non-kimberlite genesis.
Keywords: dislocation metamorphism; ore formations; fluid-explosive units; precious metals